REALIZATION OF DIDACTIC PRINCIPLES IN THE PROCESS OF FORMATION OF PROFESSIONAL AND PEDAGOGICAL MOBILITY OF THE FUTURE LECTURER - Iyevlyev, Oleksandr (Mountain School of Ukrainian Carpaty, 2019)
Training of teachers is an important task of the educational system of Ukraine. One of the ways of solving it is training future lecturer in the conditions of magistracy in higher education institution. Тhe success of the professional activity of these lecturers determines the high level of their professional and pedagogical mobility. Formation of professional and pedagogical mobility requires the use of appropriate didactic principles. It is known that the principles of training have a regulatory function in terms of modeling didactic theories and ways of regulating the practice of the educational process. According to the results of the conducted research it is necessary to use appropriate didactic principles depending on the type of component of professional and pedagogical mobility. So for the formation of the active component of professional mobility it is expedient to use the following general -addictive principles: accessibility; thoroughness; systematic and consistent. The specific principles of learning for this component should include the principles of continuity of education and the modularity of the content of training. When forming the personal component of professional mobility, it is expedient to use the following general -addictive principles: the consciousness of learning; activity and independence; the unity of educational, developmental and educational functions of training. The specific principles of teaching for this component should include the principles of humanization of education and acmeology. Part of the didactic principles can be equally effectively used to form both components of professional and pedagogical mobility, in particular the general-didactic principle of visibility and, the specific principles of mobility and coevolution. Further researches should be devoted to the substantiation of the model of formation of professional and pedagogical mobility of the future lecturer in the conditions of the magistracy.